Single-molecule force spectroscopy reveals cation-π interactions in aqueous media are highly affected by cation dehydration - Di, Weishuai (2023)
Cation-π interactions underlie many important processes in biology and materials science. However, experimental investigations of cation-π interactions in aqueous media remain challenging. Here, we studied the cation-π binding strength and mechanism by pulling two hydrophobic polymers with distinct cation binding properties, i.e., poly-pentafluorostyrene and polystyrene, in aqueous media using single-molecule force spectroscopy and nuclear magnetic resonance measurement. We found that the interaction strengths linearly depend on the cation concentrations, following the order of Li^{+}<NH_{4}^{+}<Na^{+}<K^{+}. The binding energies are 0.03-0.23  kJ mol^{-1} M^{-1}. This order is distinct from the strength of cation-π interactions in gas phase and may be caused by the different dehydration ability of the cations. Taken together, our method provides a unique perspective to investigate cation-π interactions under physiologically relevant conditions.